2009
DOI: 10.17221/3050-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Intermediately virulent Rhodococcus equi isolates from pigs in Slovenia: discovery of new plasmid types and assessment of genetic diversity by pulsed-field gel electrophoresis

Abstract: ABSTRACT:The presence of large plasmids in 30 Rhodococcus equi strains isolated from pig lymph nodes with granulomatous changes was investigated. Plasmid DNAs were isolated and digested with the restriction endonucleases BamHI, EcoRI, EcoT22I and HindIII for detailed comparison and estimation of plasmid sizes. A total of nine isolates were identified as intermediately virulent (VapB-positive), harbouring large plasmids of type 5 (n = 5) and four new variants that we tentatively designated as type 19 (n = 1), 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
(47 reference statements)
3
6
0
Order By: Relevance
“…Unfortunately, in our study complete information about the origin of each positive animal was not available. Comparison of PFGE patterns and plasmid type in this study confirmed previous observation in pigs [ 11 ], horses [ 32 ] and cattle [ 5 ] where R. equi isolates containing the same plasmid type revealed different PFGE patterns and vice versa isolates with identical PFGE patterns contained different virulence plasmids or were plasmid-less.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Unfortunately, in our study complete information about the origin of each positive animal was not available. Comparison of PFGE patterns and plasmid type in this study confirmed previous observation in pigs [ 11 ], horses [ 32 ] and cattle [ 5 ] where R. equi isolates containing the same plasmid type revealed different PFGE patterns and vice versa isolates with identical PFGE patterns contained different virulence plasmids or were plasmid-less.…”
Section: Discussionsupporting
confidence: 90%
“…Genotypic method often used in the epidemiological investigations of genetic relationships between R. equi isolates was PFGE, however, results were inconclusive [ 5 , 11 , 17 , 30 - 34 ]. In the case of R. equi infection in horses it was shown that many various strains were widespread in horse population but individual farms tended to harbor a particular single strain [ 30 - 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies on swine isolates reported much lower percentage of vapB -positive strains, in approx. 30 % [ 18 , 33 ] or 70 % of isolates [ 1 , 19 ]. The vapB -positive R. equi strains accounted for 25 to 70 % of isolates in wild boar [ 11 , 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, R. equi infection in other species than horse has aroused considerable interest due to its frequent isolation from the lymph nodes and other tissues of apparently healthy animals intended for human consumption. The prevalence of R. equi in swine carcasses varies from 0 % to over 20 % [ 1 , 2 , 11 , 18 – 20 , 28 , 31 33 ]. In wild boar the prevalence ranges from 0 % to even 52 % hunted animals [ 34 37 ], whereas in the roe deer and red deer it is lower than 1 % [ 37 ].…”
Section: Introductionmentioning
confidence: 99%